23 The virtual consultation; an established vehicle for heart failure management and communication between primary and secondary care. (6th October 2022) - Wong, B; McCambridge, J; Barrett, M; Halley, C; Ledwidge, M; McDonald, K
Abstract : Background: We have previously reported our preliminary experience showing how the heart failure (HF) virtual consultation (VC) service has been developed into a successful eHealth tool for the delivery of specialist care and a mode to transfer HF knowledge and management into the community. The service has developed and is now part of the HF care framework for Dublin and the Southeast and is part of the evolving integrated care programme for cardiovascular disease. We herein present data reflecting the evolution of this service over the last several years underlining its value in HF management Methods: Data including demographics, co-morbidity, medication, frailty, reason for referral, and the impact of the HFVC on what the GP would have done in the absence of this service, were prospectively collected on all cases discussed in VC between 2015–2021. Secondly, we collected data from the St Vincent's Hospital Group HF unit (HFU) to compare the clinical frailty score (CFS) of patients reviewed in the HFU versus the VC service. Results: Between 2015–2021, 1681 cases were discussed. Table 1 demonstrates VC baseline characteristics. Overall, most cases were New Diagnostic Case (39%), followed by Re-discussion (33%) and New Case Consultation (27%). Re-discussion cases have increased since VC first started. Mean age was 76.2 (SD 11.3) years old, with almost equal males and females (51% and 49%). In total, 333 GPs used the service. The majority of cases being discussed were from outside of Dublin (75%). VC patients were complex, with a mean of 7.1 (SD 3.4) co-morbidities, and on a mean of 9.3 (SD 4.0) medications. VC patients had a mean clinical frailty score of 3.8 (SD 1.7) which is significantly (P = 0.006) higher compared to the HFU (2.8 [SD 1.4]). In total, there were 955 (57%) medication adjustments advised, 343 (20%) echocardiograms and 145 (9%) natriuretic peptides (NP) requested as an outcome from the VC. Overall, there were 217 (13%) onward referrals of any sort. This included hospital outpatient (n = 98, 6%), HFU (n = 52, 3%) and HF specialist nurse (n = 16, 1%). Figure 1 demonstrates 'What the GP would have done if there was no VC service'. Without the VC service, there would have been 93% of onward referrals to the hospital. This would have included outpatient clinics (n =641, 50%), HFU (n = 441, 34%), and acute (n = 92, 7%) or emergency services (n = 18, 1%). Figure 2 demonstrates the incremental use of GP requested NP and echocardiography as a potential marker of improved HF diagnostic knowledge transfer to the community. Conclusions: HFVC is now established, in particular for more frail patients. There has been an increase in re-discussion cases, which demonstrates that VC can be used as a tool for continued care, in addition to a service that reduces onward hospital referrals. We have witnessed evolving practice change in community reflecting improved understanding of community HF care. This platform should be looked at in general cardiology and other chronic disease management settings.